Gastrostomy in Children: A 5-Year Single Tertiary Center Experience - Iulia Florentina Ţincu; Bianca Teodora Chenescu; Gabriel Cristian Drăgan; Anca Ioana Avram; Doina Anca Pleșca (Medicina)
Background and Objectives: Pediatric patients with complex medical conditions, including neurological impairments, genetic syndromes, dysphagia, and malnutrition, often face feeding difficulties that require enteral nutrition support. The optimal technique for gastrostomy tube (GT) placement in children remains unclear, with options such as laparoscopic gastrostomy and percutaneous endoscopic gastrostomy (PEG) being compared in previous studies. This study evaluates outcomes, including complications and caregiver satisfaction, associated with different GT placement techniques in pediatric patients, focusing on the impact of concomitant anti-reflux surgery (fundoplication). Materials and Methods: This retrospective analysis of 71 children (34 with anti-reflux surgery [Group 1], 37 without [Group 2]) undergoing GT placement between 2019 and 2024. Data included demographics, procedural details, complications, and caregiver satisfaction assessed via the Structured Satisfaction Questionnaire with Gastrostomy Feeding (SAGA-8). Results: A total of 71 patients (34 in Group 1, 37 in Group 2) were included in the final analysis. The mean age at the time of the procedure was 5.0 ± 1.1 years, with cerebral palsy being the most common underlying condition. Laparoscopic GT was performed in 97% of cases (69/71), with two percutaneous endoscopic gastrostomy (PEG) placements. Common complications included suppuration (32.35% Group 1 vs. 21.62% Group 2, p = 0.88) and infection (5.88% vs. 2.70%, p = 0.67). There were no significant differences between groups in terms of complication rates, although patients in Group 1 had longer hospitalization durations (7.51 ± 3.56 days vs. 4.22 ± 2.13 days, p < 0.005). Caregiver satisfaction, as assessed by the SAGA-8, was high, with 84.5% of families reporting positive outcomes. Factors influencing satisfaction included previous aspiration pneumonia and the use of home blenderized diets post-discharge. Conclusions: Both laparoscopic and PEG techniques are associated with low complication rates and high caregiver satisfaction in pediatric patients requiring gastrostomy placement. The laparoscopic approach may be preferred for patients undergoing concomitant fundoplication.